Food intake profiles of children aged 12, 24 and 48 months from the 2004 Pelotas (Brazil) birth cohort: an exploratory analysis using principal components - Gatica Giovanna; Barros Aluisio J D; Madruga Samanta; Matijasevich Alicia; Santos Iná S (BMC, 2012)
Abstract Objectives To identify food intake profiles of children during their first four years of life and assess its variations according to sociodemographic and behavioral characteristics. Methods The Pelotas Birth Cohort Study (Brazil) recruited 4,231 liveborns, who were followed-up at ages 3, 12, 24 and 48 months. Food consumption data of children aged 12, 24 and 48 months was collected using a list of foods consumed during a 24-hour period prior to the interview. The food profiles were identified with the use of principal component analysis (PCA) for each age studied. Results Five components were identified at each age, four of them similar in all time points, namely: beverages, milks, staple, and snacks. A meat & vegetables component was identified at 12 and 24 months and a treats component at 48 months. The greatest nutritional differences were found among children from different socioeconomic levels. With regard to the milks component, higher breast milk intake compared to cow's milk was seen among poorer children (12- and 24-month old) and higher milk and chocolate powdered milk drink consumption was seen among more affluent children aged 48 months. Poorer children of less educated mothers showed higher adherence to the treats component (48 months). Regarding to the snack component, poorer children consumed more coffee, bread/cookies while more affluent children consumed proportionately more fruits, yogurt and soft drinks. Child care outside of the home was also a factor influencing food profiles more aligned with a healthier diet. Conclusions The study results showed that very early in life children show food profiles that are strongly associated with social (maternal schooling, socioeconomic position and child care) and behavioral characteristics (breast-feeding duration, bottle-feeding and pacifier use).